2020
DOI: 10.1109/access.2020.3011483
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Study on Definition and Modeling of Service-Level Agreements for Cloud Services in IoT

Abstract: The cloud computing paradigm provides remote computing resources to the cloud service consumers and businesses. When combined with Internet of Things (IoT), both technologies open up a wide range of new possibilities for more agile and flexible applications. However, guaranteed quality of service is essential in provisioning of cloud services, which makes Service Level Agreements (SLAs) a focal point in the cloud computing and IoT ecosystem. The SLA definition and modeling phase is crucial in establishing SLAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…68 For example, a few safety contracts can bring high value and Service Level Agreements (SLAs). 69 On the other hand, various operators and companies are experimenting with low-latency offerings. For instance, Verizon is leveraging its 5G multi-access edge-computing platform through a partnership with Amazon Web Services (AWS).…”
Section: Category Basic Featuresmentioning
confidence: 99%
“…68 For example, a few safety contracts can bring high value and Service Level Agreements (SLAs). 69 On the other hand, various operators and companies are experimenting with low-latency offerings. For instance, Verizon is leveraging its 5G multi-access edge-computing platform through a partnership with Amazon Web Services (AWS).…”
Section: Category Basic Featuresmentioning
confidence: 99%
“…Literature reports on SLAs for cloud computing and IoT are numerous. The studies in [ 32 ] and [ 33 ] identified over 300 existing works related to SLAs in the domain of cloud services in IoT. To present a systematic and comprehensive literature review on the topic, authors in [ 32 ] did a systematic mapping study on management of SLAs for cloud computing and IoT and categorized their findings into various SLA stages and aspects and analyzed select reports in [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The studies in [ 32 ] and [ 33 ] identified over 300 existing works related to SLAs in the domain of cloud services in IoT. To present a systematic and comprehensive literature review on the topic, authors in [ 32 ] did a systematic mapping study on management of SLAs for cloud computing and IoT and categorized their findings into various SLA stages and aspects and analyzed select reports in [ 33 ]. However, the focus of [ 33 ] was not to compare the technical details of the existing literature, but to to analyze the existing literature and categorize the relevant reports with respect to their research contribution areas, maturity level of the evaluated contributions, tool support and application domains within cloud computing and IoT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend started roughly at the beginning of the 1990s and progressively enforced over the years, thanks to the improvements achieved by such networks in terms of performance indicators, such as timeliness, reliability, dependability and scalability. Today, this scenario is further revolutionized by the adoption of the Industrial Internet of Things (IIoT) [ 5 , 6 ] where a pervasive communication infrastructure allows connection of cloud systems, controllers, industrial equipment, sensors and actuators to dramatically improve the performance of manufacturing systems in terms of product quality, production efficiency, safety and security [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%